MENGGAGAS KEUANGAN INKLUSIF KJKS MELALUI PRODUK LASISMA DALAM MENCIPTAKAN KESEJAHTERAAN BERSAMA - Iffatul Hasanah; Ah. Shibghatullah Mujaddidi (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2020)
Financial sector services and services have not been fully enjoyed by the community, especially people living in rural areas. The village has a strategic role in contributing the maximum to national development. Villagers have a diversity of business activities and store creative economic potential in the form of business productivity and superior products produced. This if put to good use can certainly drive the motor of the national economy. In addition, villagers also often experience capital difficulties and lack of access to people in using sharia formal financial services and products and services easily and at affordable prices (Islamic financial inclusion). LASISMA (Worship-Based Services) helps lower middle-class villagers and village MSMEs facilitate cheap and affordable financial access based on easy sharia provisions and procedures. This research is quantitative research with a descriptive approach. The data was obtained by interviewing the head of the BMT branch and distributing the questionnaire to the 70 villagers who aremembers. The results showed that sharia financial inclusion in LASISMAproducts hada significant effect in creating common well-being between members and BMT. At the same time there are positive impacts before and after using LASISMA products. One of them is member growth and revenue growth both on the part of BMT and members.